Engaging Citizens through Mediation in Kaduna State, Nigeria - Melis, Eva; Esquivel-Korsiak, Victoria (World Bank, Washington, DC, 2016)
The Legal Aid Council of Nigeria (LACON) and the World Bank are pleased to present this publication about the Access to Justice for the Poor Project implemented in Kaduna State, Nigeria, between 2012 and 2015. In that time, LACON made great strides in bringing legal aid services to the grassroots and increasing access to justice by the most poor and vulnerable in our society. The Access to Justice Project offered LACON the opportunity to partner with the World Bank and learn best practices in representing clients in civil matters and community legal education. The Project helped to develop staff capacity through trainings in alternative dispute resolution and mediation, and by introducing paralegal training, all of which were novel in the Nigerian legal education. Through our partners and the use of media, we were also successful in raising awareness among the poor of their legal rights and entitlement to legal representation. Beyond benefiting affected individuals and communities, GRMs also improve development project outcomes at lower cost, help identify systemic issues, and promote accountability.8 They serve as additional useful channels of information for policy makers and implementers, and together with other accountability-enhancing mechanisms, they can contribute to raising public awareness of rights and entitlements. This is especially important where there is a lack of rights consciousness and affected individuals may not know their rights have been violated or that there are avenues for redress.